2018
DOI: 10.1016/j.jphotobiol.2017.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation by potassium iodide reveals that the anionic porphyrin TPPS4 is a surprisingly effective photosensitizer for antimicrobial photodynamic inactivation

Abstract: We recently reported that addition of the non-toxic salt, potassium iodide can potentiate antimicrobial photodynamic inactivation of a broad-spectrum of microorganisms, producing many extra logs of killing. If the photosensitizer (PS) can bind to the microbial cells, then delivering light in the presence of KI produces short-lived reactive iodine species, while if the cells are added after light the killing is caused by molecular iodine produced as a result of singlet oxygen-mediated oxidation of iodide. In an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 50 publications
(57 reference statements)
6
66
0
2
Order By: Relevance
“…We recently reported that the addition of potassium iodide dramatically potentiated the aPDI killing of Gram-negative (and Gram-positive) bacteria by photoactivated MB [9], Photofrin [8], RB [10], and TPPS4 [6]. The singlet oxygen generated could oxidize iodide anion to produce enough iodine to eradicate both Gram-positive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that the addition of potassium iodide dramatically potentiated the aPDI killing of Gram-negative (and Gram-positive) bacteria by photoactivated MB [9], Photofrin [8], RB [10], and TPPS4 [6]. The singlet oxygen generated could oxidize iodide anion to produce enough iodine to eradicate both Gram-positive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The singlet oxygen generated could oxidize iodide anion to produce enough iodine to eradicate both Gram-positive and Gram-negative bacteria. Interestingly TPPS4, which we initially assumed to be an anionic porphyrin, turned out to be cationic in character due to the two positively charged pyrrole nitrogen atoms and could bind to E. coli although it could not penetrate into the interior [6]. The mechanism of the potentiation by KSeCN appears to depend on the photochemical production of an antibacterial species formed in a reaction between the photoactivated PS and the added KSeCN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy can be applied to gram‐positive bacteria, gram‐negative bacteria and also to fungi, and is effective in animal models of localized infections . A variety of different salts can be employed, including potassium iodide , potassium bromide , sodium azide , potassium thiocyanate (KSCN) and potassium selenocyanate (KSeCN) . Potassium iodide, potassium bromide and KSCN are nontoxic; KSeCN has low toxicity, while sodium azide has moderate toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…We have also previously reported that KSeCN (at concentrations up to 100 mM) could potentiate aPDT mediated not only by MB, but also by Rose Bengal (RB) and also by 5,10,15,20‐tetrakis(4‐sulfonatophenyl)porphyrin dihydrochloride (TPPS4). We recently reported that the supposedly anionic porphyrin TPPS4 behaved more like a cationic porphyrin, and functioned as a surprisingly effective antimicrobial PS especially when potentiated by potassium iodide (KI). Considering the similarities between the chemical behaviors of thiocyanate and selenocyanate, we wanted to compare the relative activities of these two salts in potentiating aPDT bacterial killing, and investigate whether the mechanisms of action were similar or different.…”
Section: Introductionmentioning
confidence: 99%